The voice of the other: representations of the United States in Egyptian popular discourse - Pulliam, Sara (AUC Knowledge Fountain, 2012)
The Egyptian-American relationship is complex and problematic on many levels and, similar to Arab-American relations as a whole, often draws the attention of policy makers and academics within political science and its subfield of international relations. Previous analyses of this topic have focused on the dimensions surrounding US policies in the Middle East and the consequences of these policies on both the US and the Arab region. These studies range from being scathingly critical, such as Gregory's The Colonial Present, to advocating for a US foreign policy that is based in rational pursuit of interests that overlooks the discontent of the â Arab street,â as written by David Pollack. They also vary in their theoretical underpinnings; ranging from postcolonial studies, foreign policy analysis, political economy, to realist international relations and security studies. However, regardless of where they are anchored theoretically, most of these studies focus almost entirely on analyzing US actions, their effects, and providing follow-on prescription or critique directed towards the US.